The effect of incorporating lithium fluoride on the compressive strength and diametric tensile strength of glass ionomer cement - Mustafa, Ammar A.; Al-Khateeb, Khalid A. Saeed; Ismail, Ahmad Faris (Trans Tech Publications Ltd., Switzerland, 2011)
Experimental glass ionomer cement was prepared for the purpose of this study. Twenty disk specimens (16mm diameter x 10mm height) of test-GIC were prepared for the diametral tensile strength (DTS) test and twenty cylindrical specimens (6 mm diameter x 16mm height) were prepared for the compressive strength (CS) test. Specimens were stored in an artificial saliva at 37º C and (50±10%) of relative humidity in an incubator until testing. Five specimens of each GIC were submitted to CS and DTS test in each period, namely 1 hour, 24 hours, 7 days and 28 days. The specimens were tested in a Universal Testing Machine (Instron 1122, Instron corp., High Wycombe, U.K.) at a crosshead speed of 1.0mm/min for CS and 0.5mm/min for the DTS test until failure occurred. The results have revealed that incorporation of lithium fluoride in the formula of the test GIC might impart an increase in the mechanical properties of the GICs